The regime of synodality in the Eastern Church of the first millennium and its canonical basis = L’ordre synodal dans l’Église d’Orient du premier millénaire et ses fondements canoniques = L’ordine sinodale nella Chiesa d’Oriente del Primo Millennio e le sue basi canoniche - Dura, Nicolae (Ecumeny and law, 2019)
The synodal form of organisation — sought and established for His Church by Her Founder, that is, by Our Lord Jesus Christ, and affirmed by His Apostles — was also expressly reaffirmed by the canonical legislation of the Eastern Church of the first millennium.